Dynamic Response and Its Frequency Domain Characteristics of Lateritic Soil Subgrade under Traffic Load during Construction. (24th October 2020) - Bai, Wei; Mu, Kun; Kong, Lingwei; Zhang, Wenbo; Yue, Xiu
Abstract : Field tests were carried out on the compacted lateritic soil subgrade of Laibin-Mashan expressway in Guangxi Province to obtain the vertical vibration acceleration and dynamic stress amplitude of each test point under different axle loads and different driving speeds. The distribution law of the dynamic response and its frequency domain characteristics obtained by wavelet analysis emerged. The vibration of the subgrade is clearly aggravated by the increase of speed and load. Specifically, the acceleration of vehicle speed from 20 km/h to 40 km/h has a prominent effect on the vibration of subgrade, and the influence of speed on the vibration of subgrade decreases with subgrade depth. The acceleration has the greatest impact on the vibration energy in the third and fourth frequency bands.